If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 6x = 20 + 4x Solving 6 + 6x = 20 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 6x + -4x = 20 + 4x + -4x Combine like terms: 6x + -4x = 2x 6 + 2x = 20 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + 2x = 20 + 0 6 + 2x = 20 Add '-6' to each side of the equation. 6 + -6 + 2x = 20 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 20 + -6 2x = 20 + -6 Combine like terms: 20 + -6 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| 4-15=4+14 | | 7y-1=2(y+3) | | 3x+6=-25 | | 11/4+a=27/10 | | 5(-3+6n)=33+6n | | 12x^2-64=-x^4 | | 3bx-2=4ax+3 | | 7th-4=10t+14 | | -(2p+4)+8p=-p-18 | | -80+4y=4 | | 6-4r+3r=13 | | -7-3i+8-3i=0 | | 4w^2+4w+1=49 | | .5(x+40)+.1x=29 | | -8x+4=4 | | 16(x+1)=4(4x+9)-20 | | a/6+4a/8-1/3=a+3/4 | | 7x+20=-13 | | x+30=45 | | 7(2c-5)=6 | | 3(x-3)+5x=4(2x+4)-8 | | 65=5x+12 | | 7+y=-13 | | 72c-5=6 | | y-240=6(x-20) | | 4x+3-5=2x | | 4(y-5)(2y+3)=0 | | 26+(-16)+4= | | 11+3y=14 | | -(7x+3)-(-6x-8)=2 | | -1y=-20 | | 2p^2+4p-1=7p^2-7p+1 |